Interrill and rill erosion as affected by plot configuration on a sandy loam Hapludalf soil - Reichert, José Miguel; Schäfer, Marcos José; Eltz, Flávio Luiz Folleto; Norton, Lloyd Darrell (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this study was to compare rill and interrill erodibility and critical shear stress, for two configurations of soil surface: rectangular (RCS) and triangular (TCS) cross-sections. The experiment was done in 1998 on a conventionally tilled Hapludalf with a sandy loam soil surface texture. The interrill plot dimensions were 0.50 by 0.75 m, while for rill, the dimensions were 0.20 by 5.90 m for RCS, and 0.50 by 5.90 m for TCS. Constant simulated rain of 65 mm h-1 was applied on the interrill plots for 90 minutes, whereas for the rills, besides rain to prewet the soil, five extra inflows of 0.0002 m3 s-1 up to 0.0010 m3 s-1 were applied. The interrill detachment rate Di (2.09x10-4 kg m-2 s-1 for RCS and 3.35x10-4 kg m-2 s-1 for TCS), interrill erodibility Ki (1.77x106 kg s m-4 for RCS and 2.00x106 kg s m-4 for TCS), rill erodibility Kr (0.0110 kg N-1 s-1 for RCS e 0.0074 kg N-1 s-1 for TCS), and critical shear stress tc (2.61 N m-2 for RCS e 2.00 N m-2 for TCS) were not statistically different for the two cross-sections, and can be determined on any of the plot configuration for sandy loam soils.